THE STRUCTURAL, MORPHOLOGICAL AND OPTICAL STUDY OF PURE AND W-DOPEDTiO2 NANO PARTICLES AND ITS APPLICATION TO ANTIMICROBIAL ACTIVITY (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this research work, the effect of Tungsten-doping on the crystal structure, morphology and antimicrobial of titanium dioxide nanoparticles were studied. The pure and different weight % of tungsten doped TiO2 nanoparticles were synthesized by solâ€“gel method and calcinated at 600Â°C for 5 hours. The synthesised products have been characterized by X-ray Diffraction studies (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Elemental analysis (EDXA), Ultra Violet Visible Spectroscopy (UV-Vis), Photoluminescence Spectra (PL), High Resolution Transmission Spectroscopy (HRTEM) and Fourier Transform Infra Red Spectroscopy (FT-IR). XRD pattern of pure TiO2 and 1 weight % W-doped TiO2nanoparticles confirms the anatase structure and increase in the W-doping changes the phase of TiO2 to rutile. Average crystallite size of synthesized nanoparticles was determined using the Debyeâ€“Scherrer formula. The crystallite size obtained for pure TiO2 is in the range from 29 nm to 39 nm and W-doped TiO2 is varied from 28 to 34 nm. The SEM images show the agglomerated particles of spherical-like morphology. Optical property and direct bandgap of pure and W-doped TiO2nanoparticles also further characterised by UVâ€“Vis Spectroscopy. The images of HRTEM clearly confirm that particles present in the W-doped TiO2 powdered sample is nanosized particles. The Kirby Bauer Agar Well Diffusion Assay  method was employed to explore antimicrobial activity of nanosized pure and W-doped TiO2 colloidal suspension against the test microorganisms two Gram positive bacteria(Staphylococcus aureus, Bacillus subtilis),two Gram negative Bacteria(Escherichia coli, Pseudomonas aeruginosa),and two fungi(Candida albicans, Aspergillus niger). It shows that the W- doped TiO2 nanoparticles inhibited the multiplication and growth of the above mentioned test bacteria and fungi. Antimicrobial activity was found against all tested microorganisms which confirmed that W-doped TiO2 nanoparticles possess high antimicrobial activity compared to pure TiO2 nanoparticles.